Methylation detection in percutaneous lung biopsy preservation fluid: a new strategy to improve lung cancer diagnosis - Yang, Guang; Feng, Kai; Tian, Qing; Yang, Yanhong; Wang, Wenhao; Liu, Huining (Frontiers in Oncology, 2025)
IntroductionLung cancer is a significant global health threat, particularly in China, where it has high incidence and mortality rates. Current diagnostic methods face challenges, especially in obtaining sufficient tissue samples for accurate diagnosis. This study aimed to develop a new strategy using percutaneous lung biopsy preservation fluid for gene methylation detection to improve diagnostic accuracy.MethodsA total of 182 patients who underwent percutaneous lung biopsy were included in the study. The preservation fluid was replaced with a formalin-free solution for sample collection. DNA was extracted from these samples for methylation detection of SHOX2 and RASSF1A genes.ResultsThe results showed that the DNA concentration qualification rate of the preservation fluid was 98.4%, and the internal reference Ct value qualification rate was 97.6%. New cut-off values were established (▵CtSHOX2 = 6.16, ▵CtRASSF1A = 6.85). The combined methylation detection had a sensitivity of 92.8% and a specificity of 94.7%. When combined with traditional morphological pathology, the sensitivity increased to 96.0%. The methylation detection was more sensitive than traditional pathology, especially for early-stage and unclassified lung cancer patients. It also compensated for 82.6% of tissue pathology missed diagnoses. In patients with pulmonary tuberculosis, the combined methylation detection showed 75.0% sensitivity in diagnosing tuberculosis complicated with lung cancer.DiscussionIn conclusion, methylation detection in percutaneous lung biopsy preservation fluid, when combined with traditional pathology, can effectively reduce missed diagnoses and is worthy of further promotion.